EFEKTIVITAS EKSTRAK ETANOL DAUN KERSEN (Muntingia Calabura) TERHADAP PROFIL HISTOLOGI HEPAR TIKUS DIABETES - Theosobia Grace Orno; Aswiro Hasan; Fonnie Esther Hasan (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
Background: Diabetes mellitus occurs due to insulin resistance or absolute insulin deficiency as a result of damage to pancreatic beta cells. Long-term conditions of gluconeogenesis lead to auto-oxidation of glucose, protein glycation and activation of the polyol pathway which result in increased production of free radicals which is characterized by the formation of reactive oxygen compounds. Antioxidant compounds contained in Muntingia calabura L. leaves are expected to be able to protect liver cells from damage caused by free radicals with flavonoids as the dominant active compound. Aims: This study aims to test the effectiveness of Muntingia calabura L. leaf ethanol extract on the histological profile of diabetic rats.Methode:This research method is a laboratory experimental research, tissue staining using the hematoxylin eosin staining method. The result : showed that the liver histology of diabetic ratsafter therapy with ethanol extract of Muntingia calabura L. leaves at dose I, dose II and dose III did not appear to be significantly different. Similar to the group of DM rats treated with glibenclamide, the hepatocyte cells appeared to be still expe riencing enlargement, widening of the sinusoids and changes in parenchymatous cells. In addition, the ethanol extract of Muntingia calabura L. leaves dose I, II and III were also unable to regenerate the central vein. Conclusion: ethanol extract of Muntingia calabura L. leaf dose groups I, II and III were not effective in repairing hepatocyte necrosis.